Systematic analysis of funding awarded for viral hepatitis‐related research to institutions in the United Kingdom, 1997–2010. Issue 3 (22nd August 2014) - Head, M. G.; Fitchett, J. R.; Cooke, G. S.; Foster, G. R.; Atun, R.
Summary Viral hepatitis is responsible for great health, social and economic burden both globally and in the UK. This study aimed to assess the research funding awarded to UK institutions for viral hepatitis research and the relationship of funded research to clinical and public health burden of viral hepatitis. Databases and websites were systematically searched for information on infectious disease research studies funded for the period 1997–2010. Studies specifically related to viral hepatitis research were identified and categorized in terms of funding by pathogen, disease and by a research and development value chain describing the type of science. The overall data set included 6165 studies (total investment £2.6 billion) of which £76.9 million (3.0%) was directed towards viral hepatitis across 323 studies (5.2%). By pathogen, there were four studies specifically investigating hepatitis A (£3.8 million), 69 studies for hepatitis B (21.4%) with total investment of £14.7 million (19.1%) and 236 (73.1%) hepatitis C studies (£62.7 million, 81.5%). There were 4 studies investigating hepatitis G, and none specifying hepatitis D or E. By associated area, viral hepatitis and therapeutics research received £17.0 million, vaccinology £3.1 million and diagnostics £2.9 million. Preclinical research received £50.3 million (65.4%) across 173 studies, whilst implementation and operational research received £19.4 million (25.3%) across 128 studies. The UK is engaged in much hepatology research, but there are areas where the burden is great and may require greater focus, such as hepatitis E, development of a vaccine for hepatitis C, and further research into hepatitis‐associated cancers. Private sector data, and funding information from other countries, would also be useful in priority setting.